Hidden in the darkness of the Polar night: A first glimpse into winter migration of the Svalbard rock ptarmigan - Fuglei, Eva; Blanchet, Marie-Anne; Unander, Sigmund; Ims, Rolf Anker; Pedersen, Åshild Ønvik (Wildlife Biology, 2016)
Source at https://doi.org/10.2981/wlb.00241 Among many unknown aspects of the Svalbard rock ptarmigan’s biology is whether the birds migrate seasonally within the Svalbard archipelago. Visual observations in spring and fall have indicated that they could perform long-range migration, a behaviour that would allow them to track seasonal shifts in suitable feeding areas. However, the movement patterns and habitat use of the Svalbard rock ptarmigan has until now been hidden in the dark of the Polar winter making visual observations almost impossible. The most effective method for gathering reliable data about bird migrations and overwintering areas is to use satellite telemetry. Here we report on the first application of satellite telemetry on rock ptarmigan. Our aim was to investigate the performance of satellite tags on ptarmigan and to collect information about the timing of migration, migration distances and directions as well as the location of winter areas. Satellite tags were mounted on 21 birds in May, but due to technical malfunctioning, we obtained post-breeding migration data only from four birds (three females and one male). The three females remained at the breeding area until 17–27 September where after they migrated. The male made an excursion movement from his summer range before he migrated 17 September. The migration distances were in the range of 30 to 149 km, and their migrations were in different direction from the breeding locality. After this migration, the ptarmigan remained in the wintering areas until all of them died before the spring migration. The observations are consistent with previous suggestions that Svalbard rock ptarmigan undertake migrations to winter areas as a strategy to cope with spatially patchy and temporally unpredictable distribution of good feeding habitats in winter.